Effect of Root and Mycelia on Fine Root Decomposition and Release of Carbon and Nitrogen Under Artemisia halodendron in a Semi-arid Sandy Grassland in China - Liu, Xinping; Luo, Yongqing; Cheng, Li; Hu, Hongjiao; Wang, Youhan; Du, Zhong (Frontiers in Plant Science, 2021)
Plant fine root turnover is a continuous process both spatially and temporally, and fine root decomposition is affected by many biotic and abiotic factors. However, the effect of the living roots and the associated mycorrhizal fungal mycelia on fine root decomposition remains unclear. Thus, we aim to explore the influence of these biotic factors on fine root decomposition in a semi-arid ecosystem. In this study, we investigated the effect of fine roots and mycelia on fine root decomposition of a pioneer shrub (Artemisia halodendron) in Horqin sandy land, northeast China, by the ingrowth core method combined with the litterbag method. Litterbags were installed in cores. Core a allowed the growth of both fine roots and mycelia (treatment R+M), core b only allowed the growth of mycelia (treatment M), and in core c the fine root and mycelia growth was restricted and only bulk soil was present (treatment S). The process of root decomposition was significantly affected by the living roots and mycelia, and carbon (C) and nitrogen (N) concentration dynamics during root decomposition differed among treatments. Mycelia significantly stimulated the mass loss and C and N release during root decomposition. R+M significantly stimulated the accumulation of soil total C, total N and organic N under litterbags. The mycelia significantly stimulated the accumulation of the inorganic N (ammonium-N and nitrate-N) but the presence of fine roots weakened nitrate-N accumulation. The presence of living root and associated mycelia strongly affected the process of root decomposition and matter release in the litter-soil system. This result should strengthen the understanding of root-soil interactions.